Radiation of piezoelectric rings into the air through cylindrical waveguides - PAJEWSKI, W.; KIEŁCZYŃSKI, P.; SZALEWSKI, M. (Archives of Acoustics, 1995)
In the paper the results of the investigations of the radiation of piezoelectric rings into the air through solid (e.g. glass, plexiglass, aluminium) cylinders are presented. The obtained radiation patterns approximate Bessel distribution. In the case of short cylinders the vibrations are more complicated, one obtains zero-order Bessel function with several zero-crossings. For long cylinders Bessel function is truncated, the quantity of sidelobes is reduced. The obtained results show that the configurations: piezoelectric ring-cylinder can be applied as ultrasonic transducers with narrow beam with limited diffraction in certain range. The additional advantage of this construction is the increase of vibration amplitude on the transducer axis, the disadvantage - small frequency bandwidth.